2015
DOI: 10.1089/fpd.2014.1847
|View full text |Cite
|
Sign up to set email alerts
|

High Occurrence of Extended-Spectrum β-Lactamase-ProducingSalmonellain Broiler Carcasses from Poultry Slaughterhouses in South Korea

Abstract: The emergence of antibiotic-resistant foodborne Salmonella has become a major public health problem. Consumption of undercooked poultry contaminated with Salmonella can induce food poisoning in humans. In this study, we investigated the occurrence and antibiotic resistance patterns of Salmonella spp. isolated from 120 chicken carcasses produced in 6 poultry slaughterhouses in South Korea. A total of 11 samples (9.2%) were found contaminated with Salmonella: 5 isolates were serotyped as Salmonella Bellevue stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…In our study, the overall Salmonella prevalence was 25.8% in chicken slaughterhouses, which was higher than that in Nepal (14.5%), Spain (17.9%), South Africa (19.2%), Brazil (2.7%), or Korea (9.2%, 21.7%) (Chung and others ; Van Nierop and others ; Maharjan and others ; Capita and others ; Medeiros and others ; Chon and others ). However, the overall Salmonella prevalence found in this study was lower to that in Portugal (60%) or Thailand (57%) (Antunes and others ; Padungtod and Kaneene ).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In our study, the overall Salmonella prevalence was 25.8% in chicken slaughterhouses, which was higher than that in Nepal (14.5%), Spain (17.9%), South Africa (19.2%), Brazil (2.7%), or Korea (9.2%, 21.7%) (Chung and others ; Van Nierop and others ; Maharjan and others ; Capita and others ; Medeiros and others ; Chon and others ). However, the overall Salmonella prevalence found in this study was lower to that in Portugal (60%) or Thailand (57%) (Antunes and others ; Padungtod and Kaneene ).…”
Section: Discussioncontrasting
confidence: 43%
“…Our results also showed that 22% of Salmonella isolates tested were ESBL‐producers. Previous studies in Korea have reported that ESBL CTX‐M‐15‐producers account for 9.2% of Salmonella isolates cultured from chicken carcasses of poultry slaughterhouses and 29% of Salmonella isolates cultured from retail chicken meat (Choi and others ; Chon and others ). The prevalence of ESBL‐producing Salmonella isolates in Korea merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising because there have been numerous reports of ESBL-producing Enterobacteriaceae in food sources, especially poultry products (27-29). It is also known that resistant Enterobacteriaceae (i.e., salmonellosis) in food can be transmitted within the community (30, 31). The only one ESBL-producing bacteria detected in this study was Chryseobacterium meningosepticum (E3), a non- Enterobacteriaceae that is known to cause meningitis and pneumonia in patients with compromised immune systems (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of antimicrobial-resistance in Salmonella strains has been reported in Korea [5, 24]. Antimicrobial resistance and virulence of Salmonella strains play an important role in systemic infections with these pathogens [14].…”
Section: Introductionmentioning
confidence: 99%